A meta-analysis of the therapeutic effect of gefitinib combined with chemotherapy and chemotherapy alone in treating non-small cell lung cancer. Issue 31 (31st July 2020) - Zhao, Qingda; Sun, Kai; Lei, Xuemei; Cai, Le
Abstract: Background: Whether the combination of gefitinib and chemotherapy is beneficial for advanced non-small cell lung cancer (NSCLC) remains controversial. This study aimed to summarize the currently available evidence and compare the efficacy and safety of gefitinib combined with chemotherapy versus chemotherapy alone for treating advanced NSCLC. Methods: Literature on comparing the effects of gefitinib combined with chemotherapy and chemotherapy alone in treating NSCLC was retrieved from the PubMed, EMBASE and Cochrane Database. The primary outcome measures included progression-free survival (PFS) and overall survival (OS). Revman 5.3 was used for data processing. Results: Seven randomized controlled trials were included, involving a total of 1418 patients. There appeared a significant improvement in PFS (hazard ratio (HR) = 0.60 [95% CI 0.43, 0.82], P  = .001) after treatment with gefitinib combined with chemotherapy when compared with chemotherapy alone. The subgroup analysis showed a significant advantage of sequential administration (HR = 0.67 [95% CI 0.57, 0.79], P  < .00001). There was no significant improvement in OS (HR = 0.92 [95% CI 0.71, 1.20], P  = .54), and no significant improvement in overall response rate (ORR) (HR = 0.98 [95% CI 0.67, 1.44], P  = .93). The risks of rash and diarrhea (odds ratios) were higher in gefitinib combined with chemotherapy group when compared with chemotherapy alone, and there were significant differences on grade 3/4 rash and thrombocytopenia between 2 groups. Conclusion: Gefitinib combined with chemotherapy is superior to chemotherapy alone in PFS, sequential administration prolongs the patients' PFS, however, a survival advantage is not shown in OS or ORR. Gefitinib combined with chemotherapy aggravates rash, diarrhea and thrombocytopenia. Abstract : Supplemental Digital Content is available in the text